Strategies for the cure of HIV infection - Rodríguez-Muñoz, Jesús; Moreno, Santiago (Enfermedades infecciosas y microbiologia clinica, 2019)
The disadvantages of the long-term administration of antiretroviral therapy as well as the huge number of affected persons have placed the cure of HIV as a primary goal of Public Health. HIV may persist in the organism by at least four mechanisms: a latently infected cellular reservoir, the persistent replication of HIV in spite of ART, anatomic sanctuaries, and the immune dysfunction. Several strategies directed against these mechanisms have been developed. With all this, a complete eradication of HIV has been achieved in a patient using the transplantation of haemopoietic stem cells that were resistant to HIV-infection, and there are examples of functional cure either spontaneously (elite controllers) or after antiretroviral therapy (post-treatment controllers). However, no strategies have been successful in reducing the reservoir size, nor in achieving constant, uniform remissions. The failure of isolated strategies makes it likely that the combination of several of them may be the future solution.